Factors relating to and impacting eGovernment readiness in South Africa : a case of the Western Cape Government - Noruwana, Nimrod (GSB: Faculty, 2015)
Information and Communication Technologies (ICTs) have become increasingly important in enabling governments to deliver services to their citizens. Developing countries have limited understanding of what needs to be in place for governments to be considered ready for the implementation of eGovernment projects. As a result, most developing countries embark on these projects inadequately prepared, which results in failure. Large sums of money are spent on eGovernment initiatives which do not provide the envisaged benefit for citizens and businesses. This study therefore discusses factors influencing eGovernment initiatives by governments to improve services to their citizens, businesses and among their constituents. It further examines the stage of readiness of the South African government in implementing eGovernment initiatives to improve its services. The discussion uses Actor Network Theory (ANT) and in particular the concepts of 'moments of translation' and 'irreversibility' as a lens through which to understand and interpret the social phenomenon. Although a number of eGovernment researchers have argued that strong leadership and clear vision are required to implement eGovernment initiatives, the view is that governments have continuously failed to achieve the intended results. eGovernment potentials which are well documented in Information Systems and eGovernment research literature have not been institutionalised by governments to derive benefits due to limited capabilities in the administration of the public service. The study used ANT as the underpinning theory. A deductive approach with interviews was used for data collection in a selected provincial government (of the Western Cape) in South Africa. The outcome of this study is a general framework of readiness for eGovernment initiatives in South Africa, and more generally, Africa, to guide and determine the stage of readiness for eGovernment initiatives to achieve the intended results. This research contributes the application of the moments of translation and irreversibility of ANT as a lens through which the interplay between role players of socially constructed phenomena such as eGovernment readiness can be studied. Other forms of contribution are the application of an iterative process to moments of translation, and institutionalisation of each stage of moments of translation, during the implementation of eGovernment projects.